Impact of group visits for older patients with heart failure on advance care planning outcomes: Preliminary data. Issue 10 (2nd June 2021) - Ahluwalia, Sangeeta C.; Bandini, Julia I.; Coulourides Kogan, Alexis; Bekelman, David B.; Olsen, Bonnie; Phillips, Jessica; Sudore, Rebecca L.
Abstract: Objective: Advance care planning (ACP) is critically important for heart failure patients, yet important challenges exist. Group visits can be a helpful way to engage patients and caregivers in identifying values and preferences for future care in a resource‐efficient way. We sought to evaluate the impact of group visits for ACP among older adults with heart failure and their caregivers on ACP‐related outcomes. Methods: We conducted a mixed‐methods pilot study evaluating the impact of an ACP group visit for older adults with heart failure and their caregivers on ACP‐related outcomes including readiness and self‐efficacy. The evidence‐based PREPARE for Your Care video‐based intervention was used to guide the group visits. Twenty patients and 10 caregivers attended one of the five 90‐min group visits led by a trained facilitator. Group visit participants completed pre‐, post‐, and 1‐month follow‐up surveys using validated 5‐point ACP readiness and self‐efficacy scales. Qualitative feedback obtained within 3 days of a group visit was analyzed using a directed content analysis. Results: Patient participants had a median age of 78 years. Approximately half were female while caregiver participants were mostly female. Participants were predominantly white. Patient readiness scores improved significantly pre‐to‐post (+0.53; p = 0.002) but was not sustained at 1‐month follow‐up. Patient and caregiver self‐efficacy showed some improvement pre‐to‐post but was also not sustained at follow‐up. Interviews revealed positive impacts of group visits across the three themes: encouraging reviewing or revisiting prior ACP activities, motivating patients to take direct steps towards ACP, and serving as a "wake‐up" call to action. Conclusions: Disease‐focused group visits may have a short‐term effect on ACP outcomes but ongoing touchpoints are likely necessary to sustain ACP over time. The results highlight a need for follow‐up ACP conversations after a single group visit. Timing for follow‐ups and the ideal person to follow‐up ACP conversations needs to be explored.